2018
DOI: 10.1161/circimaging.117.007146
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Aortic Valve Calcium Scoring in Patients With Aortic Stenosis

Abstract: URL: http://www.clinicaltrials.gov. Unique identifiers: NCT01358513, NCT02132026, NCT00338676, NCT00647088, NCT01679431.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(209 citation statements)
references
References 19 publications
8
198
1
2
Order By: Relevance
“…43 Sex-specific cutoffs (>2000 Agatston units in men and >1300 in women) 43 recently were shown to be more closely associated with outcomes than echocardiographic parameters of aortic stenosis severity in a large multicenter registry. 44 Furthermore, the additional information obtained from a computed tomography study (severity of calcification of the valves, aortic annulus, aorta, mitral annulus, and coronary vessels) is important for procedural planning and for the assessment of other potential complications that can arise from valve interventions.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…43 Sex-specific cutoffs (>2000 Agatston units in men and >1300 in women) 43 recently were shown to be more closely associated with outcomes than echocardiographic parameters of aortic stenosis severity in a large multicenter registry. 44 Furthermore, the additional information obtained from a computed tomography study (severity of calcification of the valves, aortic annulus, aorta, mitral annulus, and coronary vessels) is important for procedural planning and for the assessment of other potential complications that can arise from valve interventions.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Because some studies have suggested sex-based differences in AVC severity, we repeated the analysis using sexspecific thresholds to identify severe AVC (>1200 AU for women and >2000 AU for men). 13,14 Higher T LV-Ao was still significantly associated with severe AVC (OR, 1.13; P = .01) (eTable 2 in the Supplement). When we subdivided T LV-Ao by median, patients with T LV-Ao greater than 66 milliseconds were 2.3 times more likely to demonstrate severe AVC.…”
Section: Diagnostic Ability Of T Lv-ao For Significant Av Calcificationmentioning
confidence: 97%
“…The identified region on chromosome 12 displays an intronic variant in the CRADD gene as a top marker. Variation mapping to CRADD has been previously related to coronary artery calcification 27 , a phenotype strongly linked to calcific aortic valve disease and aortic stenosis 28 . The PheWAS data for rs71190365 indicate a link to known cardiac comorbidities such as forced expiratory volume and body mass, which may represent a pleiotropic effect-decreased area of the aortic valve is a determinant of cardiac output which governs cardiac output and exercise capacity 29 .…”
Section: Discussionmentioning
confidence: 99%